SiC 세라믹스의 균열치유거동 및 부식특성 - 황진량(Jin Ryang Hwang); 김대웅(Dae Woong Kim); 남기우(Ki Woo Nam) (Han-guk haeyang gonghak hoeji (Online), 2013)
The crack-healing behavior and corrosion resistance of SiC ceramics were investigated. Heat treatments were carried out from $900^{°}C$ to $1300^{°}C$. A corrosion test of SiC was carried out in acid and alkaline solutions under KSL1607. The results showed that heat treatment in air could significantly increase the strength. The heat-treatment temperature has a profound influence on the extent of crack healing and the degree of strength recovery. The optimum heat-treatment temperature was $1100^{°}C$ for one hour at an atmospheric level. In the two kinds of solutions, the cracks in a specimen were reduced with increasing time, and the surface of the crack healed specimen had a greater number of black and white spots. The strength of the corroded cracked specimen was similar to that of the cracked specimen. The strength of the corroded crack healed specimen decreased 47% and 75% compared to that of the crack healed specimen in the acid and alkaline solutions, respectively. Therefore, the corrosion of SiC ceramics is faster in an alkaline solution than in an acid solution.